2011
DOI: 10.1007/s10071-011-0383-8
|View full text |Cite
|
Sign up to set email alerts
|

Adult but not juvenile Barbary macaques spontaneously recognize group members from pictures

Abstract: For group-living animals, it is crucial to distinguish one’s own group members from those of other groups. Studies applying operant conditioning revealed that monkeys living in relatively small groups are able to recognize their own group members when tested with photographs of group members and other conspecifics. Employing a simple looking time paradigm, we here show that Barbary macaques living in two social groups comprising 46 and 57 individuals, respectively, at the enclosure ‘La Forêt des Singes’ at Roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
0
39
1
Order By: Relevance
“…To determine the experimental partners (close friend or nonfriend) for the social experiments, we relied on group scans (minimum n = 255 per season for the GB and PB groups; Supplemental Experimental Procedures, section 3) during which we recorded the occurrence of grooming and affiliative proximity (<1 m). For the photograph experiments [10] (infants, close friend, or non-friend), the experimenter sat down in front of the male or female subject with a covered photo on a clipboard and initiated the trial by uncovering the photo while videotaping the subjects' behavioral response. Trials lasted until the subject left or ceased looking at the picture for 1 min (Supplemental Experimental Procedures, section 4; Movie S6).…”
Section: Experimental Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the experimental partners (close friend or nonfriend) for the social experiments, we relied on group scans (minimum n = 255 per season for the GB and PB groups; Supplemental Experimental Procedures, section 3) during which we recorded the occurrence of grooming and affiliative proximity (<1 m). For the photograph experiments [10] (infants, close friend, or non-friend), the experimenter sat down in front of the male or female subject with a covered photo on a clipboard and initiated the trial by uncovering the photo while videotaping the subjects' behavioral response. Trials lasted until the subject left or ceased looking at the picture for 1 min (Supplemental Experimental Procedures, section 4; Movie S6).…”
Section: Experimental Design and Data Collectionmentioning
confidence: 99%
“…In order to determine potential age-related changes in social interest, we presented male and female subjects with portrait photographs [10] of newborn Barbary macaques, a close friend or a non-friend (Supplemental Experimental Procedures, sections 3 and 4). Note that in this species, females maintain close bonds with both related and unrelated females [11], and males interact with infants remarkably frequently [12].…”
Section: Social Interestmentioning
confidence: 99%
“…1a). Previous studies suggest that monkeys (Pokorny & de Waal, 2009; Schell et al, 2011), including rhesus macaques (Sliwa et al, 2011), match photographs of conspecifics to their real-life counterparts. Studies at Cayo Santiago (Higham et al, 2011) and elsewhere (Waitt et al, 2003, 2006) have already used photographs to investigate sexual signaling preferences in rhesus macaques.…”
Section: 0 Experiments 1: Males and Females Viewing Male Scrotamentioning
confidence: 99%
“…That previous study found that monkeys might take a keen interest in photographs and study them intently; it also indicated that the older subjects generally showed less interest in the pictures than did the juveniles. However, the adults distinguished between pictures of members of a neighboring group and pictures of members of their own group (revealing a higher interest in the out-group members), while the juveniles did not [30] . In the study by Almeling et al [7] on motivational changes in old age, male and female subjects were presented photographs of newborn conspecifics, a close "friend," or a "non-friend," as defined by the frequency of affiliative interactions.…”
Section: Motivational Shifts In Aging Barbary Macaquesmentioning
confidence: 99%
“…To assess age-related changes in social interest, we adopted a protocol established by Schell et al [30] , which consists of the presentation of portrait photographs of conspecifics and recording their responses using a video camera for later analysis (blinded to the condition) of the animals' responses and looking times on a frame-byframe basis. That previous study found that monkeys might take a keen interest in photographs and study them intently; it also indicated that the older subjects generally showed less interest in the pictures than did the juveniles.…”
Section: Motivational Shifts In Aging Barbary Macaquesmentioning
confidence: 99%